Synthesis of Nitrogen-Phosphorus Flame Retardant and Its Flame-Retardant Application in Epoxy Resin - Chen, William; Nilsson, Emma; antos, Isabella S (Journal of Green Energy and Environmental Engineering, 2023)
A novel multielement synergistic flame retardant (DAI) was successfully synthesized via a two-step reaction using 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 2-aminobenzothiazole (ABZ), and indole-3-carboxaldehyde (I3C). The successful synthesis of DAI was confirmed by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. Subsequently, epoxy resin (EP) composites, namely EP/DAI-3, EP/DAI-5, and EP/DAI-7, were prepared by blending DAI with EP via a thermosetting method. The flame-retardant properties and residual char characteristics after combustion of the prepared EP composites were investigated. The results demonstrated that the prepared EP composites exhibited excellent smoke suppression and flame-retardant performance. Particularly, EP incorporating 7 wt% DAI showed significant reductions of 34.5%, 32.3%, and 42.2% in peak heat release rate (pHRR), peak CO production rate (pCOPR), and peak CO₂ production rate (pCO₂PR), respectively. Compared with pure EP, EP/DAI-7 achieved a limiting oxygen index (LOI) value of 32.6% and attained a V-0 rating in the UL-94 test. Char residue analysis revealed that the char layer of EP/DAI-7 was denser and more robust than that of pure EP, with an ID/IG value of 2.03, indicating the highest degree of graphitization.